MODOMICS: a database of RNA modifications and related information : 2025 update and 20th anniversary - Sordyl, Dominik; Boileau, Etienne; Bernat, Agata; Maiti, Satyabrata; Mukherjee, Sunandan; Moafinejad, S Naeim; Farsani, Masoud Amiri; Shavina, Anastasiya; Cappannini, Andrea; Agostini, Giada; Conticello, Silvestro G; Stefaniak, Filip; et al. (Nucleic acids research, 2025)
MODOMICS is the reference database of RNA modifications and related information, integrating chemical, biochemical, structural, and functional data. In this 2025 update, marking the 20th anniversary of MODOMICS, the database has been significantly expanded in scope and depth. The RNA sequence section now includes transcriptome-wide data generated in collaboration with Sci-ModoM, a quantitative resource of high-throughput epitranscriptomic datasets, enabling the representation of >48 000 transcripts with high-confidence modification annotations. The catalog of modified residues was improved with systematic curation, and addition of new computational descriptors derived from quantum mechanical calculations. An all-versus-all similarity analysis of chemical structures was performed, and the results are provided as an interactive similarity graph to explore chemical relationships among modifications. The protein section has been updated with newly characterized enzymes and expanded annotations of modification pathways, supported by an improved evidence and reliability framework. Together, these advances further strengthen MODOMICS as a comprehensive and reliable community resource, serving as both a reference and a platform for discovery in the rapidly developing field of epitranscriptomics. MODOMICS is available at https://iimcb.genesilico.pl/modomics/.
Gesehen am 14.01.2026